Dynamic bookmarking of primary response genes by p300 and RNA polymerase II complexes - Byun, Jung S. (2009)
Profiling the dynamic interaction of p300 with proximal promoters of human T cells identified a class of genes that rapidly coassemble p300 and RNA polymerase II (pol II) following mitogen stimulation. Several of these p300 targets are immediate early genes, including FOS, implicating a prominent role for p300 in the control of primary genetic responses. The recruitment of p300 and pol II rapidly transitions to the assembly of several elongation factors, including the positive transcriptional elongation factor (P-TEFb), the bromodomain-containing protein (BRD4), and the elongin-like eleven nineteen lysine-rich leukemia protein (ELL). However, transcription at many of these rapidly induced genes is transient, wherein swift departure of P-TEFb, BRD4, and ELL coincides with termination of transcriptional elongation. Unexpectedly, both p300 and pol II remain accumulated or "bookmarked" at the proximal promoter long after transcription has terminated, demarking a clear mechanistic separation between the recruitment and elongation phases of transcription in vivo. The bookmarked pol II is depleted of both serine-2 and serine-5 phosphorylation of its C-terminal domain and remains proximally positioned at the promoter for hours. Surprisingly, these p300/pol II bookmarked genes can be readily reactivated, and elongation factors can be reassembled by subsequent addition of nonmitogenic agents that, alone, have minimal effects on transcription in the absence of prior preconditioning by mitogen stimulation. These findings suggest that p300 is likely to play an important role in biological processes in which transcriptional bookmarking or preconditioning influences cellular growth and development through the dynamic priming of genes for response to rechallenge by secondary stimuli.